Design and Development of a Haptic Device Prototype for 3D Virtual Environments - Stephan Plaschke (2011)
In the last decade, presentation and rendering of virtual 3D environments have reached a great degree of realism. Stereoscopic displays and projections provide a spatial impression or even immersion. Combined with 3D sound systems the effect is further enhanced. In contrast, haptic rendering and interaction still is mainly an area of research. Few systems convey a tactile or kinesthesia perception by imposing pressure upon small areas of the human skin or by exerting force on muscles and joints. This master thesis deals with requirements and construction of a kinesthetic system in a 1D force-feedback setup. Along with the design and development phase requirements are given for an installation in a CAVE.